Strengthening Effective Parenting Practices over the Long-Term: Effects of a Preventive Intervention for Parentally Bereaved Families - Hagan, Melissa J. (2012)
This study tested the effect of the Family Bereavement Program (FBP), a preventive intervention for bereaved families, on effective parenting (e.g. caregiver warmth, consistent discipline) six years after program completion. Families (n=101; 69% female caregivers; 77% Caucasian, 11% Hispanic) with children between ages 8–16 who had experienced the death of one parent were randomized to the FBP (n=54) or a literature control condition (n=47). Multiple regression analyses conducted within a multilevel framework indicated that the FBP had a significant positive impact on a multi-rater, multi-measure assessment of parenting at 6-year follow-up, controlling for pretest levels of parenting and child mental health problems. Mediation analyses showed that short-term program effects on parenting, including caregiver warmth and effective discipline, significantly mediated the impact of the FBP on effective parenting six years later. These findings indicate that a relatively cost-effective brief intervention for families who experienced a major stressor resulted in sustained effects on caregiver warmth and consistent discipline six years following the program.